Cost–utility analysis for platinum-sensitive recurrent ovarian cancer therapy in South Korea: results of the polyethylene glycolated liposomal doxorubicin/carboplatin sequencing model - Lee HY; Yang BM; Hong JM; Lee TJ; Kim BG; Kim JW; Kim YT; Kim YM; Kang S (Dove Medical Press, 2013)
Hwa-young Lee,1 Bong-Min Yang,1 Ji-min Hong,1 Tae-Jin Lee,1 Byoung-Gie Kim,2 Jae-Weon Kim,3 Young-Tae Kim,4 Yong-Man Kim,5 Sokbom Kang61Graduate School of Public Health, Seoul National University, Seoul, South Korea; 2Department of Obstetrics and Gynecology, Samsung Medical Center, Seoul, South Korea; 3Department of Obstetrics and Gynecology, Seoul National University, Seoul, South Korea; 4Department of Obstetrics and Gynecology, Yonsei University, Seoul, South Korea; 5Department of Obstetrics and Gynecology, University of Ulsan, Ulsan, South Korea; 6Department of Obstetrics and Gynecology, National Cancer Center, Kyeonggi-do, South KoreaObjective: We performed a cost–utility analysis to assess the cost-effectiveness of a chemotherapy sequence including a combination of polyethylene glycolated liposomal doxorubicin (PLD)/carboplatin versus paclitaxel/carboplatin as a second-line treatment in women with platinum-sensitive ovarian cancer.Methods: A Markov model was constructed with a 10-year time horizon. The treatment sequence consisted of first- to sixth-line chemotherapies and best supportive care (BSC) before death. Cycle length, a time interval for efficacy evaluation of chemotherapy, was 9 weeks. The model consisted of four health states: responsive, progressive, clinical remission, and death. At any given time, a patient may have remained on a current therapy or made a transition to the next therapy or death. Median time to progressions and overall survivals data were obtained through a systematic literature review and were pooled using a meta-analytical approach. If unavailable, this was elicited from an expert panel (eg, BSC). These outcomes were converted to transition probabilities using an appropriate formula. Direct costs included drug-acquisition costs for chemotherapies, premedication, adverse-event treatment and monitoring, efficacy evaluation, BSC, drug administration, and follow-up tests during remission. Indirect costs were transportation expenses. Utilities were also derived from the literature. Costs and utilities were discounted at an annual rate of 5% per cycle.Results: PLD/carboplatin combination as the second line in the sequence is more effective and costly than paclitaxel/carboplatin combination, showing an additional US$21,658 per quality-adjusted life years. This result was robust in a deterministic sensitivity analysis except when median time to progression of second-line therapies and administration cost of PLD/carboplatin per administration cycle were varied. The probability of cost-effectiveness for PLD/carboplatin combination was 49.4% at a willingness to pay $20,000.Conclusion: A PLD/carboplatin combination is an economically valuable option as second-line chemotherapy for the treatment of platinum-sensitive ovarian cancer in South Korea.Keywords: cost, utility, Markov modeling, ovarian cancer, chemotherapy